Engineering Secure Future Internet Services and Systems Current Research - Heisel, Maritta; Joosen, Wouter; López, Javier; Martinelli, Fabio (Security and Cryptology, 2014)
This State-of-the-Art Survey contains a selection of papers representing state-of-the-art results in the engineering of secure software-based Future Internet services and systems, produced by the NESSoS project researchers. The engineering approach of the Network of Excellence NESSoS, funded by the European Commission, is based on the principle of addressing security concerns from the very beginning in all software development phases, thus contributing to reduce the amount of software vulnerabilities and enabling the systematic treatment of security needs through the engineering process. The 15 papers included in this volume deal with the main NESSoS research areas: security requirements for Future Internet services; creating secure service architectures and secure service design; supporting programming environments for secure and composable services; enabling security assurance and integrating former results in a risk-aware and cost-aware software life-cycle.